The Impact of Agile Methodology Implementation on Software Quality in Information System Development A Case Study of Industry X - Muhammad Galih Ramaputra; Hendri Purnomo; Seli Puri Andini (Universitas Islam Kuantan Singingi, 2026)
The rapid demand for high-quality software requires organizations to adopt adaptive and efficient development methodologies. This study examines the impact of Agile methodology adoption on software quality within information system development in Industry X. Utilizing a quantitative explanatory design, data were collected via questionnaires from 100 software development team members and analyzed using simple linear regression. Descriptive analysis indicates that both Agile implementation (mean = 4.14) and software quality (mean = 4.09) fall into the high category. Hypothesis testing confirms that Agile methodology has a positive and significant effect on software quality (β = 0.68, t-count = 11.33, p < 0.001), contributing 52% to its variance (R² = 0.52). While team collaboration and functional suitability emerged as the strongest contributors, customer engagement and performance efficiency received the lowest scores. These findings imply that robust Agile practices substantially elevate system quality. To maximize outcomes, organizations must strategically intensify user participation throughout the development cycles and reinforce rigorous performance testing.